2022
DOI: 10.1101/2022.09.13.507820
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Regenerative MRL/MpJ Tendon Cells Exhibit Sex Differences in Morphology, Proliferation, Mechanosensitivity, and Cell-Matrix Remodeling

Abstract: Clinical and animal studies have reported the influence of sex on the incidence and progression of tendinopathy, which results in disparate structural and biomechanical outcomes. However, there remains a paucity in our understanding of the sex-specific biological mechanisms underlying effective tendon healing. To overcome this hurdle, our group has investigated the impact of sex on tendon regeneration using the super-healer Murphy Roths Large (MRL/MpJ) mouse strain. Despite a shared scarless healing capacity, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 53 publications
0
1
0
Order By: Relevance
“…We have recently shown that adult male and female MRL/MpJ tendons both demonstrate a regenerative capacity with vastly improved mechanical recovery compared to those of B6 mice (13). More recently, we also found that both male and female MRL/MpJ tenocytes exhibit similar or superior in vitro outcome measures, as detailed in the present study, compared to B6 tenocytes (64). These findings suggest that the cellular and molecular mechanisms underlying MRL/MpJ tendon regeneration are largely conserved between sexes.…”
Section: Discussionsupporting
confidence: 83%
“…We have recently shown that adult male and female MRL/MpJ tendons both demonstrate a regenerative capacity with vastly improved mechanical recovery compared to those of B6 mice (13). More recently, we also found that both male and female MRL/MpJ tenocytes exhibit similar or superior in vitro outcome measures, as detailed in the present study, compared to B6 tenocytes (64). These findings suggest that the cellular and molecular mechanisms underlying MRL/MpJ tendon regeneration are largely conserved between sexes.…”
Section: Discussionsupporting
confidence: 83%
“…Our recent work has shown that B6 and MRL/MpJ tendon cells cultured on commercial 3D nanofiber scaffolds elicit distinct cellular responses to anisotropic and isotropic surface topographies associated with homeostasis and wound healing, respectively. 50 To gain further insight into how the interplay between the biochemical and structural properties of the ECM regulate cell activity, future studies could augment these biomaterial-based approaches by applying the dECM as a surface coating.…”
Section: Discussionmentioning
confidence: 99%